Harmonisations of Shari'ah and Civil Law: progress and achievements - Mohd, Azizah (Centris, IIUM, 2024)
The harmonisation of Shari’ah and Civil law is not a recent development, especially in Malaysia. This concept has not been newly introduced but has rather evolved informally alongside the enactment and development of laws. The reason is that both Shari’ah and Civil law share the same spirit and objective i.e., the establishment of justice.